Multiple Sclerosis Therapy Consensus Group (MSTCG): position statement on disease-modifying therapies for multiple sclerosis (white paper). (August 2021) - Wiendl, Heinz; Gold, Ralf; Berger, Thomas; Derfuss, Tobias; Linker, Ralf; Mäurer, Mathias; Aktas, Orhan; Baum, Karl; Berghoff, Martin; Bittner, Stefan; Chan, Andrew; Czaplinski, Adam; et al.
Multiple sclerosis is a complex, autoimmune-mediated disease of the central nervous system characterized by inflammatory demyelination and axonal/neuronal damage. The approval of various disease-modifying therapies and our increased understanding of disease mechanisms and evolution in recent years have significantly changed the prognosis and course of the disease. This update of the Multiple Sclerosis Therapy Consensus Group treatment recommendation focuses on the most important recommendations for disease-modifying therapies of multiple sclerosis in 2021. Our recommendations are based on current scientific evidence and apply to those medications approved in wide parts of Europe, particularly German-speaking countries (Germany, Austria, and Switzerland).